Photocatalytic activity under visible light region of ca-modified TiO2 np films prepared by sparking off ca-electroplated ti tips - Nidchamon Jumrus (2018)
© 2018 World Scientific Publishing Company. In this work, calcium (Ca)-modified titanium dioxide (TiO2) nanoparticulate (NP) films were successfully prepared using sparking off Ca-electroplated Ti tips. Aqueous solution of calcium carbonate (CaCO3) was used as electrolyte in the electroplating process. The experiment was carried out using electric current of 0.02mA applied to titanium electrodes for 10min. The NP films with small and uniform size were deposited on quartz substrate using the sparking process with a high DC voltage of 4kV in ambient air. The as-deposited NP films were then annealed at 800°C, 900°C and 1000°C for 3h under atmospheric pressure to improve their crystallinity. Morphology, structural and optical properties of the NP films were characterized by SEM, XRD, Raman, XPS and UV-Vis spectroscopy. The effects of annealing temperature on the properties of the as-deposited and annealed NP films were reported. Furthermore, photocatalytic activity against 10 μM of methylene blue (MB) under visible light region will be discussed.